2003
DOI: 10.1034/j.1600-0447.108.s419.1.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacological treatment with lithium and antiepileptic drugs: suggested guidelines from the Danish Psychiatric Association and the Child and Adolescent Psychiatric Association in Denmark

Abstract: A subcommittee under the Danish Psychiatric Association and the Child and Adolescent Psychiatric Association in Denmark have recently developed national guidelines for the psychopharmacological treatment with lithium and antiepileptic drugs, and the present translation aims at contributing to the international discussion on the development of proper guidelines for the treatment of bipolar disorder. Among the antiepileptic drugs, the report deals with valproate, carbamazepine and lamotrigine and to a lesser ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 78 publications
0
63
1
1
Order By: Relevance
“…32,33 The Danish Psychiatric Association recommends prophylaxis if a patient has had 2 episodes in less than 5 years. 34 All these differ from earlier recommendations of prophylaxis for patients either after 3 episodes, or 2 episodes within 2 years. Using actuarial techniques, Grof et al 35 concluded that at least 2 episodes of mania or depression within 2 years was the best criterion, as this correctly classified 61% of patients as having a future recurrence of illness or not (55% of patients were predicted to have a recurrence within 2 years and they did [true positives] and 6% of patients were predicted not to have a recurrence and they did not [true negatives]).…”
Section: Initiation and Selection Of Long-term Treatmentcontrasting
confidence: 41%
See 2 more Smart Citations
“…32,33 The Danish Psychiatric Association recommends prophylaxis if a patient has had 2 episodes in less than 5 years. 34 All these differ from earlier recommendations of prophylaxis for patients either after 3 episodes, or 2 episodes within 2 years. Using actuarial techniques, Grof et al 35 concluded that at least 2 episodes of mania or depression within 2 years was the best criterion, as this correctly classified 61% of patients as having a future recurrence of illness or not (55% of patients were predicted to have a recurrence within 2 years and they did [true positives] and 6% of patients were predicted not to have a recurrence and they did not [true negatives]).…”
Section: Initiation and Selection Of Long-term Treatmentcontrasting
confidence: 41%
“…If there is recurrence of illness after slowly tapering off of prophylactic medication, then prophylactic treatment should be resumed and continued for many years, or possibly be lifelong. 34 Unfortunately, this appears to be a somewhat arbitrary time frame and does not address individual patient differences, such as number and severity of episodes, suicidality, and degree of impaired functioning. Impaired functioning is frequently related to residual symptoms and may be an indication that treatment needs to be not only continued but also optimized to ensure that the patient achieves complete remission.…”
Section: How Long Should An Effective Treatment Be Continued?mentioning
confidence: 99%
See 1 more Smart Citation
“…The World Federation of Societies of Biological Psychiatry suggest that SR preparations may have advantages for tolerability, whereas guidelines from Denmark state that diarrhea may be improved by changing from an SR to an IR preparation. 11,12 These contradictory statements leave the prescriber uncertain about how to dose lithium in a way that optimizes its tolerability profile.…”
Section: Limitationsmentioning
confidence: 99%
“…However, most existing international clinical practice guidelines on the management of BAD provide limited and somewhat contradictory recommendations regarding lithium dosing. 6,7,[10][11][12] For example, the American Psychiatric Association states that SDD regimens may improve peak-related adverse effects, such as tremor, help manage polyuria, and facilitate compliance. 7 However, they also state that lithium is usually started in divided doses to minimize adverse effects.…”
Section: Limitationsmentioning
confidence: 99%